UJI ANTIINFLAMASI FRAKSI ETIL ASETAT KULIT KAYU AKWAY (Drymis piperita) ASAL PAPUA PADA TIKUS (Ratus norvegicus) JANTAN - Rani Dewi Pratiwi; Elsye Gunawan (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
This study aimed to test the anti-inflammatory effect of ethyl acetate fraction of akway bark (Drymis piperita) on male mice (Hundred norvegicus) and look at pain responses in test animals. The use of akway bark by the local community by boiling and boiling water is then drunk, there are also local people who directly use by chewing. Akway bark anti-inflammatory test and pain response to male rats with a test sample concentration of 200 mg/kg. The method to be used in the study for anti-inflammatory test of akway bark is by the formation of artificial inflammation in the soles of the left foot of male rats while the pain response method uses the Tail flick Method. The test animals were made in 3 groups in each test with a total of 5 heads per group. Group 1 was given positive control (anti-inflammatory testing using mefenamic acid, while pain response test using Na Diclofenac), group 2 was given negative control (CMC) and and group 3 was given a test solution. The test results showed anti-inflammatory activity of ethyl acetate fraction of the skin had anti-inflammatory activity with a percent anti-inflammatory power of 48.47%, while percent pain resistance of ethyl acetate fraction of the bark akway by 33.02%.